Effects of expander conditioning on the nutritional value of diets with dried distillers grains with solubles in nursery and finishing pigs - Feoli, C.; Gugle, Terry L.; Carter, S.D.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Three experiments were conducted to determine the effects of expander conditioning on nutritional value of diets without and with corn- and sorghum-based dried distillers grains with solubles (DDGS). In Exp. 1, 180 nursery pigs (average weight 29 lb) were assigned to 30 pens. Treatments were arranged as a 3 × 2 factorial with main effects of diet formulation (corn-soybean meal vs. 30% corn- or sorghum-based DDGS) and conditioning (standard steam vs. expander) prior to pelleting. Pigs fed corn-soybean meal diets had better (P < 0.005) ADG, F/G, and digestibility of DM, N, and GE than pigs fed diets with DDGS. Diets with corn-based DDGS supported better (P < 0.03) ADG, F/G, and digestibility of DM and N than diets with sorghum-based DDGS. Expander processing improved (P < 0.009) ADG, F/G, and digestibility of DM, N, and GE compared with standard conditioning. Pigs fed diets with sorghum-based DDGS showed the greatest response in F/G to expander conditioning leading to a DDGS source × conditioning interaction (P < 0.008). In Exp. 2, 176 finishing pigs (average weight 164 lb) were assigned to 16 pens. Treatments were arranged as a 2 × 2 factorial with main effects of diet formulation (corn-soybean meal vs. 40% sorghum-based DDGS) and conditioning (standard steam vs. ex-pander) prior to pelleting. Net electrical energy required for feed processing was lower (P < 0.001) and production rate was greater (P < 0.005) for the corn-soybean meal diets than for diets with DDGS. However, pellet durability was improved (P < 0.001) by addition of DDGS to the diets. Pigs fed corn-soybean meal diets had better (P < 0.03) overall ADG and F/G than pigs fed diets with DDGS. Expander conditioning did not affect ADG (P > 0.83) but improved overall F/G and dressing percentage (P < 0.007). In Exp. 3, 192 finishing pigs (average weight 222 lb) were assigned to 16 pens to determine nutrient digestibility. Treatments were the same as in Exp. 2. Feed and water was consumed ad libitum during a 6-d adjustment period; then, feces were collected for 2 d. Corn-soybean meal diets had greater (P < 0.001) digestibility of DM, N, and GE than diets with DDGS, and expander conditioning improved (P < 0.02) digestibility of DM, N, and GE compared with standard conditioning. However, the improved digestibility of DM with expander conditioning was apparent primarily for the DDGS diets (diet × conditioning interaction, P < 0.01). In conclusion, expanding diets improved ADG, F/G, and nutrient digestibility in nursery pigs and F/G, dressing percentage, and nutrient digestibility in finishing pigs fed diets without and with DDGS.
Keywords: Digestibility; Dried distillers grains with solubles; Expander conditioning